Adaptasi Agama Katolik terhadap Kearifan Lokal Hamis Batar di Kabupaten Malaka - Marianus Teti (Publisher STPKat, 2024)
The type of research used is qualitative research using a descriptive qualitative approach. The method used is the ethnographic research method. This data was collected by the author through a team of data collectors, all of whom came from each tribe in Malacca Regency. Not all tribes in Malacca Regency are interviewed, but in terms of sabate saladi customs, hamis batar ceremonies or rituals in the Fehan plains there are similarities. The results of the interview show that the adaptation of Catholicism to the local wisdom of Hamis Batar in Malacca Regency is a tradition of celebrating the corn harvest which has been passed down from generation to generation from ancestral times to the present, especially the first harvest at the beginning of the year/called batar tinan. There is an adaptation of Catholicism to the local wisdom of Hamis Batar in Malacca Regency, namely that the teachings of the Catholic Church are not conflicted with human traditions because the church was also born from human cultural traditions. There are similarities in the meaning of hamis batar with the Eucharistic prayer in the Eucharist celebration. The Hamis Batar ceremony is an expression of gratitude from the people for the results given by God.